Analisis Aksiologi Filsafat Islam dalam Pembentukan Nilai-Nilai Moral di PTQ Cahaya Nusantara - Rohmah, Mar-Atin Nabila; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
This study aims to analyze the application of axiological values in Islamic philosophy to the development of moral values among students (santri) at PTQ Cahaya Nusantara. The research is grounded in the urgency of moral education as a foundation for shaping student character based on Islamic values. A descriptive qualitative approach was employed using a case study design. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed thematically. The findings indicate that moral values are instilled through daily adab habituation, teacher role modeling, the integration of adab and nature-based curricula, and the use of prophetic stories as instructional media. Educators adhere to the principle that adab precedes knowledge, aligning with the axiological values of Islam rooted in divine revelation and the character of Prophet Muhammad (peace be upon him). Challenges such as lack of discipline and teacher inconsistency are addressed through internal strategies, including intensive mentoring and enhancement of Qur’anic memorization. The study concludes that PTQ Cahaya Nusantara has successfully integrated axiological principles of Islamic philosophy into its educational system, contributing positively to the sustainable and contextual formation of student character and morality.